Twiddler's syndrome in children: an unusual cause of pacemaker failure. Issue 2 (February 1995) - Abrams, S.; Peart, I.
Abstract : Mechanical causes of pacemaker failure are well recognised. Twiddler's syndrome leading to pacemaker failure has been previously recognised in adults, but there have been no published reports of its occurring in children. Two cases leading to failure of the pacing system are reported. In the first twiddling led to fracture of the lead and in the second it led to displacement of the lead from the heart. Children may be more susceptible to twiddler's syndrome because they have thinner subcutaneous tissues, making leads more accessible, and their comprehension of the consequences may be poor.